Nanomechanics of Carbon Nanotubes. Issue 1 (December 2013) - Sun, Y.W.; Dunstan, D.J.; Hartmann, M.A.; Holec, D.
Abstract We discuss the mechanical properties of carbon nanotubes, in particular the pressure‐dependence of the Raman modes and the collapse pressure, and their relation to the corresponding mechanical properties of graphite and graphene. The frequencies of the Raman G‐mode and radial breathing mode (RBM), as well as the pressure dependence of the RBM can be largely‐explained in the existing framework of C–C stretching modes and envirionmental effects induced by the pressure medium. The pressure dependence of the G‐mode is still missing such an explanation. The collapse pressure can be understood in terms of the continuum theory for thin‐walled tubes. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)